2022
DOI: 10.1029/2021jf006502
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost Thermal Dynamics and Cryostratigraphy at Villum Research Station, Station Nord, Eastern North Greenland (81°N)

Abstract: We provide the northernmost permafrost thermal analysis in Greenland through the ground temperature time series (2014–2021) and cryostratigraphy of two 20‐m deep boreholes (SN1 and SN2) at Villum Research Station, Station Nord (81°N). Three sedimentary units are identified in the stratigraphy: glacial, glaciomarine, and beach deposits. These sandy and gravelly deposits are interpreted to comprise a deglaciation and isostatic emergence sequence. Ice‐poor epigenetic permafrost grew downwards into the deposits fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Air temperature warming has been observed at many Arctic sites, with Svalbard showing generally higher rates than the Arctic average (Isaksen et al., 2022b). However, other sites in the High Arctic showed similar rates, such as Station Nord in Greenland with 0.08°C/year, 1990–2020 (Strand et al., 2022). For Svalbard specifically, Isaksen et al.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Air temperature warming has been observed at many Arctic sites, with Svalbard showing generally higher rates than the Arctic average (Isaksen et al., 2022b). However, other sites in the High Arctic showed similar rates, such as Station Nord in Greenland with 0.08°C/year, 1990–2020 (Strand et al., 2022). For Svalbard specifically, Isaksen et al.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, this effect may also be site specific. A study of cold permafrost near Station Nord, Greenland, revealed permafrost warming rates of 0.07 and 0.05°C/year in two boreholes at 20 m depth for the recent period of 2014–2021 (Strand et al., 2022). Similarly, a study from the western Russian Arctic found increased permafrost warming in recent years (Vasiliev et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation